2018
DOI: 10.1080/17429145.2018.1542041
|View full text |Cite
|
Sign up to set email alerts
|

IAA and flavonoids modulates the association between maize roots and phytostimulant endophytic Aspergillus fumigatus greenish

Abstract: The association between microbes and plant roots involves a complex chemical dialogue featured by IAA and flavonoids in addition to other signals. Current study is focused on the role of IAA and flavonoids as essential elements of the chemical dialogue between an endophytic fungus and maize roots. The strain was isolated from the leaves of Withania somnifera and was identified as Aspergillus fumigatus greenish by 18S rDNA sequence. Culture filtrate of the strain contained phyotstimulant (IAA, ammonia and ACC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 49 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…28,29 However, all the fungal isolates produce IAA revealing that IAA might be a factor of fungi to communicate with plants. [30][31][32][33] Therefore, it is required in minimum concentration. Similarly, phosphate solubilizing activities assist the in-vivo plant growth condition.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 However, all the fungal isolates produce IAA revealing that IAA might be a factor of fungi to communicate with plants. [30][31][32][33] Therefore, it is required in minimum concentration. Similarly, phosphate solubilizing activities assist the in-vivo plant growth condition.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inhibition of GA 3 , IAA and Transzeatin levels were high in the seedlings. IAA (Mehmood et al, 2018) and Tranzeatin (Kabbara et al, 2018) are involved to have a role in the accommodation of fungal colonization on host plant roots. As opposed, in the seedling of maize where GA 3 was high (control seedlings treated with BIPOL SD (OD 0.6 )), the BIPOL colonization was hindered.…”
Section: Discussionmentioning
confidence: 99%
“…These osmolytes have positive effects on enzyme and membrane integrity, along with adaptive roles in mediating osmotic adjustment in plants subjected to stress conditions [107]. In another investigation, 2,3-butanediol was found to induce plant production of nitric oxide (NO) and hydrogen peroxide [108], and it was reported that NO regulates antioxidant enzymes at the level of activity and gene expression [109]. At the same time, the plant hormone SA is required for plant growth under abiotic stress [7,17,73].…”
Section: Discussionmentioning
confidence: 98%